Potential Adoption of Smart Living and Universal Design for Aging Population Wellbeing in Malaysian Housing Development: A Systematic Literature Review - Syafiq Johari; Muzani Mustapa; Fara Mustapa (Environmental Science and Sustainable Development)
The rapid growth of the ageing population triggers the demand for innovative solutions to support independent living for seniors, given the changes in physical health, cognitive function, and mobility. Smart Living and Universal Design principles are trusted to play crucial roles in improving the quality of life, especially for the elderly and disabled individuals. Hence, this paper aims to present a theoretical background on the potential adoption of smart living and universal design in housing development in response to cater to the ageing population’s well-being. A systematic literature review utilizing bibliometric analysis through the visualization of similarity viewer software is conducted to synthesise existing research on smart living and universal design housing features catering to the ageing population. Findings highlighted the potential for extensive smart living and universal design adoption in housing, with several challenges derived from the lack of standard regulations. Despite the drawbacks, the incorporation of extensive smart living and universal design is noteworthy for its efficacy in extending the life expectancy of the ageing population, particularly the elderly residing in their residences. This study provides practical implications for policymakers, designers, and practitioners to implement smart living and universal design in Malaysian housing development to foster the ageing population well-being in Malaysia.